A study of social well-being among university students - Sining, Ma; Sharaai, Amir Hamzah; Wafa, Wafaurahman (Springer Nature, 2022)
Purpose: There are social, psychological, and different health dimensions that affect social well-being in university life. Hence, the objective of the study was to identify the potential social impacts (students’ health and safety, discrimination, feedback, privacy, transparency, and end-of-life responsibility which is further planned) that affect social well-being in the organization and analyze the correlation of social impacts from the beginning until the end of the cycle in the teaching and learning process. Methods: The research was carried out with reference to “Social Organization LCA (SO-LCA), a new approach to the implementation of S-LCA,” as well as ISO 14040 and ISO 14044 guidelines. This research was conducted in a selected university in Malaysia. A survey was conducted using a questionnaire. The items in the questionnaire have been adopted based on the S-LCA UNEP guideline and adapted by SO-LCA. The items were validated by expert panels. A pilot study was conducted to a small group of sample to check the reliability of the items used in the questionnaire. The questionnaire was validated, and the pilot study was conducted to check the reliability of the instrument. The questionnaire was distributed to a sample of respondent (n = 228) using proportional stratification sampling technique. Results and discussion:The study found that the department in the selected university positively impacted their students’ well-being. Nonetheless, marginal issues were detected, for instance, discrimination to the students, stress, including feedback systems of the local communities. The study found that suicide has a positive relationship with stress, age, gender, sexual, and disabled discrimination. The correlation coefficient between pressure and suicide was .226 (p < .01). The r-value of .226 implied a weak correlation. Meanwhile, the correlation coefficients between suicide with gender discrimination, sexual discrimination, and disability discrimination were valued at .224, .193, and .224, respectively, indicating weak correlations (p < .01). However, according to the feedback mechanism and privacy, some students complain results for courses are not confidential. However, the result shows that the students planning to pursue studies at the same university and at the department, consequently, students were satisfied with the services provided by the university. Conclusion:This study has shown that the department from this university positively impacted their students’ well-being. Nonetheless, there were marginal aspects like discrimination, stress among students, and feedback mechanisms that need to be reviewed and improved. The research recommends improving the feedback mechanism by providing timely feedback and designing multiple ways of anonymous feedback.